2020
DOI: 10.3390/ijerph17041321
|View full text |Cite
|
Sign up to set email alerts
|

Food Retail Environments in Greater Melbourne 2008–2016: Longitudinal Analysis of Intra-City Variation in Density and Healthiness of Food Outlets

Abstract: Obesity prevalence is inequitably distributed across geographic areas. Food environments may contribute to health disparities, yet little is known about how food environments are evolving over time and how this may influence dietary intake and weight. This study aimed to analyse intra-city variation in density and healthiness of food outlets between 2008 and 2016 in Melbourne, Australia. Food outlet data were classified by location, type and healthiness. Local government areas (LGAs) were classified into four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 44 publications
0
47
0
1
Order By: Relevance
“…True exemplars could well be the subset of countries that have seen improvements in undernutrition without the unintended consequences of overweight and obesity at population level, a phenomenon now being observed in most LMICs ( 32 ). In addition to known associations between overweight/obesity and the food environment ( 33 ), a few evaluations have shown that food distribution and school feeding programs themselves, intended to address undernutrition, could contribute to the growth in child overweight and obesity ( 34 , 35 ). Future studies should include these complexities in the mix of determining true exemplars, especially in regions of the world with a growing double burden of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…True exemplars could well be the subset of countries that have seen improvements in undernutrition without the unintended consequences of overweight and obesity at population level, a phenomenon now being observed in most LMICs ( 32 ). In addition to known associations between overweight/obesity and the food environment ( 33 ), a few evaluations have shown that food distribution and school feeding programs themselves, intended to address undernutrition, could contribute to the growth in child overweight and obesity ( 34 , 35 ). Future studies should include these complexities in the mix of determining true exemplars, especially in regions of the world with a growing double burden of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The FES uses a classification system and 20-point scoring tool, ranging from −10 (least healthy) to +10 (mostly healthy) [ 33 ]. For the current study, the food outlet ‘healthiness’ classifications were based on a recent Australian study, which used an adapted FES classification and health score [ 34 ]. Using the adapted FES, food outlets were classified into 18 food outlet types [ 34 ], scored and classed by ‘healthiness’ into three groups: healthy (FES range +5 to +10); less healthy (FES range −4 to +4) and unhealthy (FES range −10 to −5).…”
Section: Methodsmentioning
confidence: 99%
“…For the current study, the food outlet ‘healthiness’ classifications were based on a recent Australian study, which used an adapted FES classification and health score [ 34 ]. Using the adapted FES, food outlets were classified into 18 food outlet types [ 34 ], scored and classed by ‘healthiness’ into three groups: healthy (FES range +5 to +10); less healthy (FES range −4 to +4) and unhealthy (FES range −10 to −5). Classification, scoring and grouping were conducted by three university-qualified dietitians (JM, TW, SJ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers were not logged into personal UberEats accounts to avoid biased results. This project focused on evaluation of the 202 independent takeaways identified from the previous study using the Food Environment Score Tool [ 16 , 29 , 30 ]. Independent takeaways have been defined as outlets that are not franchises, which prepare and sell meals or snacks, ready for immediate consumption, e.g., local kebab shop [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have described the nutritional composition of meals from takeaway franchises (chain stores that prepare and sell meals/snacks ready for immediate consumption, offered in specialised packaging, e.g., McDonalds ® , or KFC ® ) that are subject to menu labelling [ 14 , 15 ]. However, independent takeaways (takeaway outlets that are not franchises, e.g., local kebab shop) [ 16 ], are not subject to this regulation and were reported to be the second largest (30%) food outlet type on OFD platforms after takeaway franchises [ 10 ]. Only a few studies have explored the nutritional quality of food items provided by independent outlets [ 5 , 10 , 17 ], highlighting a research gap exists for this food outlet classification.…”
Section: Introductionmentioning
confidence: 99%